Peningkatan Soft Skill Penulisan Artikel Ilmiah Dan Publikasi Bagi Mahasiswa STIT Ahlussunnah Bukittinggi - Edriagus Saputra; Yosi Aryanti; M. Yemmardotillah (Universitas PGRI Palembang, 2023)
The purpose of implementing this community service program is to increase interest in writing for students and increase student scientific publications, so that after completing the final project (thesis) they can write an article from the results of their research. This service activity is packaged in the form of a training given to students. STIT Ahlussunnah Bukittinggi, which was carried out by a Lecturer at the West Sumatran Islamic Institute of Pariaman with a Lecturer at STIT Ahlussunnah Bukittinggi. The method of implementing activities in the form of delivering material, assignments and practicum given to participants, namely (a) Research Methodology, (b) Writing Scientific Articles, (c) Using Reference and Plagiarism, (d) submitting articles to journals. The results of the Community Service program are given to students in the form of training. It can be concluded, if viewed from the level of understanding of the participants, that is, 88% really understand the material presented. Meanwhile, in terms of carrying out the tasks of the resource persons, 60% of the participants have successfully submitted articles to the campus journals.